SURVEY ANALYSIS OF THE BRITISH DEFENSE CONTRACTOR ‘BABCOCK INTERNATIONAL’ - E. O. Savchenko (Plekhanov Russian University of Economics, 2020)
The article describes the current standing of the British defense contractor ‘Babcock International’ and estimates prospects of the business development. Today we can see the rising importance of military means, which makes research and analysis of defense complex companies more acute, as they are responsible for technical realization of military tools for foreign policy of states. Academic literature pays more attention to American companies, which can be explained by their influence on the market and leading positions in the field of R & D. According to the authors, other companies, for instance ‘Babcock International’, a large British company of the sector, should also be studied. It can provide a more comprehensive view of the current standing of defense complex companies in the West and prospects of their further development. In spite of the Fact that defense expenditure of Western countries restored growth after a long period of cut-back, the authors’ analysis shows certain negative trends (which could step up) for ‘Babcock International’ business. These trends refer to other medium-size companies of Western military complex. A conclusion can be made about a coming wave of consolidation of this sector companies in the near future, mainly on the national level, which could lead to closing-down of unprofitable enterprises and mass reduction of jobs, as well as degrading technological and other related competences.